Art and Aesthetics in the Thought of María Zambrano - Ochoa Pineda, Amada Cesibel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This work tries to find hermeneutical keys of the thought of María Zambrano, of her ideas on painting and poetry from the hypothesis that the philosopher from Malaga establishes a productive and fruitful dialogue with the European thought of the 20th century, which leads her to coin an original philosophy. Zambrano, throughout her writings, moves from the vital reason of Ortega y Gasset to her peculiar meaning of situated poetic reason, which deals with a delimited scope of objects and contributes to laying the foundations for an aesthetic of the poetic and the pictorial as a creative element of human life.